Weapons for Victory : The Hiroshima Decision Fifty Years Later - Cooper, Barry, 1943- (Book collections on Project MUSE., 2004)
"In the ongoing conversations among specialists in terrorist studies, as well as the ordinary discourse of citizens in western democracies wishing to understand the world around them, this book will add a distinctive voice."--Jacket.